The influnce of internal marketing on organizational commitment of resident and district office, Samarahan division/ Othman Let - Let, Othman (2008)
The research is to determine the level of related internal marketing variables which might have significant effect on the organizational commitment of Resident and District Office, Samarahan Division. The research also aimed to find the association between the internal marketing variables and the organizational commitment of Resident and District Office, Samarahan Division. The result of the study reveals that there is significant association between the level of the internal marketing variables and the organizational commitment of employee of Resident and District Office, Samarahan Division.